PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) PADA SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN ALAT KONTRASEPSI (STUDI KASUS: PUSKESMAS KECAMATAN RAMAN UTARA) - Wulan Kurnia Safitri; Ossy Dwi Endah Wulansari; Akmal Junaidi; Aristoteles Aristoteles (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
The choice of contraception is very important. Usually, the acceptors choose the contraceptive that is easiest to use even though the device is not necessarily in accordance with the existing variables, causing errors in the selection of contraceptives and resulting in the failure of the family planning program. This study aims to build a decision support system that can assist in the selection of contraceptives. This study uses the Simple Additive Weighting (SAW) method using 7 criteria variables and a web-based system built. The results of the research conducted indicate that the decision support system built can help provide contraceptive recommendations based on calculations using 7 criteria. Other tests show that the functions contained in the system have been running well according to user needs.